'Go home to the second wave!': Discourses of trans inclusion and exclusion in a queer women's online community. (December 2022) - Bailey, Aimee
Abstract: As the visibility of trans movements has increased in recent years, so too has the antagonism between trans rights supporters and some sections of the feminist and lesbian communities (Phipps, 2016; Hines, 2017, Pearce et al., 2020). This antagonism is especially pronounced in digital spaces, where online discussions have fuelled an increasing polarisation of the debate (Hines, 2017). This paper examines the representation of trans identities on Autostraddle: a popular entertainment, news and lifestyle website for lesbian and bisexual women. It focuses on the longest and most controversial comment thread in the 2-million-word Queer Women's Advice Corpus. The thread is a response to a guide to dating trans women for cis women. Using a combination of critical discourse analysis, sociocultural linguistics and corpus linguistics, I unpack the argumentation strategies (Fairclough and Fairclough, 2012) that commenters use to construct stances on the inclusion of trans women in the queer women's online space. The major strategies include persuasive definitions of lesbian, imaginaries about trans women's hypothetical bodies and the illegitimation of trans-exclusionary commenters as bad feminists and community outsiders. I find that that trans inclusion is successfully negotiated on a community level, but that trans women are still problematised on an intimate level due to their (imagined) genitalia. Trans women are 'hyperembodied' in the data, with the presence or absence of a penis acting as the focal point for inclusion and desirability.